Why should I switch on my camera? Developing the cognitive skills of compassionate communications for online group/teamwork management - Jayasundara, J. M. P. V. K.; Gilbert, Theo; Kersten, Saskia; Meng, Li (Frontiers in Psychology, 2023)
Students' social and academic disconnection was heightened as a result of the pandemic-driven transition to online platforms in Higher Education (HE) irrespective of the pre-planning or readiness of teachers or learners. Many students are reluctant to turn on their video cameras to be more present with others during online group meetings. In relation to group/teamwork, compassion is defined as noticing, not normalising, one's own or others' distress or disadvantage and acting wisely to prevent or reduce it. In order to gauge levels of both inclusion and criticality within a group, this understanding of compassion is evaluated in the HE sector utilising task-focused in-class group work meetings that were video recorded. This study examines a) the application of compassionate communication techniques (created in and for the offline classroom) and; b) their effects on virtual group meetings which are video recorded. In this mixed-methods study, task-focused group meetings were video recorded before and after an online interactive 90-min training session (the intervention) in the Cognitive Skills of Compassionate Communications (CSCC) for teams. Each group (𝑛 = 4), of the total sample of six groups (𝑛 = 24) consisted of Science, Technology, Engineering and Mathematics (STEM) students and these were drawn from a sample of five Sri Lankan universities. The quantitative data analyses of the pre-and post-CSCC intervention task-focused meetings indicated a significant improvement in students' screen-gaze attentiveness to one another, after the CSCC intervention. For the analysis of the data, R, SPSS and Microsoft Excel were used. The qualitative data analysis informed these apparent changes in students' motivation to turn on their cameras during group meetings.